2011
DOI: 10.1042/bj20101726
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interaction and functional regulation of connexin50 gap junctions by calmodulin

Abstract: Cx50 (connexin50), a member of the α-family of gap junction proteins expressed in the lens of the eye, has been shown to be essential for normal lens development. In the present study, we identified a CaMBD [CaM (calmodulin)-binding domain] (residues 141–166) in the intracellular loop of Cx50. Elevations in intracellular Ca2+ concentration effected a 95 % decline in gj (junctional conductance) of Cx50 in N2a cells that is likely to be mediated by CaM, because inclusion of the CaM inhibitor calmidazolium preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
65
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 57 publications
(91 reference statements)
4
65
0
Order By: Relevance
“…Moreover, injection of the proteo-liposome further showed that the Cx26 channel can be regulated by intracellular Ca 2+ [42], a result consistent with a previous findings [43]. The channel activities we reported are a net of outward minus inward activities.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, injection of the proteo-liposome further showed that the Cx26 channel can be regulated by intracellular Ca 2+ [42], a result consistent with a previous findings [43]. The channel activities we reported are a net of outward minus inward activities.…”
Section: Discussionsupporting
confidence: 87%
“…This mutant can even interact with CaM without Ca 2+ -activation of CaM possibly due to an increase in overall positive charges of Cx46 IL domain. This result also agrees with the study by Chen et al (2011) (29), which shows that several positively charged residues on Cx50 are important for Cx50-CaM interaction.…”
Section: Discussionsupporting
confidence: 83%
“…CaM has been implicated in mediating the Ca 2ϩ -dependent regulation of gap junctions via interacting directly with the intracellular domains of connexins (13,18,19 (Fig. 5A).…”
mentioning
confidence: 99%
“…CaM is a Ca 2ϩ -binding protein that acts by transducing the effect of a rise in intracellular Ca 2ϩ to create physiological responses; specifically it has been implicated in mediating the Ca 2ϩ -dependent down-regulation of Cx32 gap junction channels (18,19). Cx32 has been shown to interact with CaM directly via the Cx32CT domain in a Ca 2ϩ -dependent manner (13).…”
mentioning
confidence: 99%